Centre-excised X-ray luminosity as an efficient mass proxy for future galaxy cluster surveys. Issue 3 (2nd October 2017) - Mantz, Adam B.; Allen, Steven W.; Morris, R. Glenn; von der Linden, Anja
Abstract: The cosmological constraining power of modern galaxy cluster catalogues can be improved by obtaining low-scatter mass proxy measurements for even a small fraction of sources. In the context of large upcoming surveys that will reveal the cluster population down to the group scale and out to high redshifts, efficient strategies for obtaining such mass proxies will be valuable. In this work, we use high-quality weak-lensing and X-ray mass estimates for massive clusters in current X-ray-selected catalogues to revisit the scaling relations of the projected, centre-excised X-ray luminosity ( L ce ), which previous work suggests correlates tightly with total mass. Our data confirm that this is the case with L ce having an intrinsic scatter at fixed mass comparable to that of gas mass, temperature or Y X . Compared to the other proxies, however, L ce is less susceptible to systematic uncertainties due to background modelling, and can be measured precisely with shorter exposures. This opens up the possibility of using L ce to estimate masses for large numbers of clusters discovered by new X-ray surveys (e.g. eROSITA) directly from the survey data, as well as for clusters discovered at other wavelengths with relatively short follow-up observations. We describe a simple procedure for making such estimates from X-ray surface brightness data, and comment on the spatial resolution required to apply this method as a function of cluster mass and redshift. We also explore the potential impact of Chandra and XMM–Newton follow-up observations over the next decade on dark energy constraints from new cluster surveys.